Proceedings of the 12th Annual Conference on Genetic and Evolutionary Computation 2010
DOI: 10.1145/1830483.1830507
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of division of labor in genetically homogenous groups

Abstract: Within nature, the success of many organisms, including certain species of insects, mammals, slime molds, and bacteria, is attributed to their performance of division of labor, where individuals specialize on specific roles and cooperate to survive. The evolution of division of labor is challenging to study because of the slow pace of biological evolution and imperfect historical data. In this paper, we use digital evolution to evolve groups of clonal organisms that exhibit division of labor. We then investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Other researchers have studied task-related division of labor, wherein individuals cells cooperate to perform specialized tasks efficiently, as a mechanism by which multicellularity can arise (Michod, 2007). Goldsby et al (2010) investigated task-related division of labor within the Avida platform and found that digital organisms are capable of selecting specialized roles in groups using both spatial information and inter-organism communication.…”
Section: Multicellularity and Digital Platformsmentioning
confidence: 99%
“…Other researchers have studied task-related division of labor, wherein individuals cells cooperate to perform specialized tasks efficiently, as a mechanism by which multicellularity can arise (Michod, 2007). Goldsby et al (2010) investigated task-related division of labor within the Avida platform and found that digital organisms are capable of selecting specialized roles in groups using both spatial information and inter-organism communication.…”
Section: Multicellularity and Digital Platformsmentioning
confidence: 99%
“…Classic (as in off-line) evolutionary robotics has already been used as a tool to explore important issues such as the nature of self-organized regulation mechanisms (Waibel et al, 2006;Duarte et al, 2011Duarte et al, , 2012aLichocki et al, 2012;Ferrante et al, 2015), the benefits of communication (Trianni et al, 2007;Goldsby et al, 2010), the importance of coordination (Bernard et al, 2016b), and the trade-off between evolving polymorphic and monomorphic populations (Waibel et al, 2009;Bernard et al, 2015Bernard et al, , 2016aTuci and Rabérin, 2015). However, embodied evolutionary robotics poses a problem on its own as mating and reproduction are performed in situ, meaning that how and where interactions between individuals are performed actually influence the course of evolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, most research focus on the particular case of homogeneous groups of individuals (Waibel et al, 2009) as is classic in evolutionary robotics. This means that the individuals are forced to rely on phenotypical plasticity (Waibel et al, 2006;Ferrante et al, 2015;Eskridge et al, 2015) and/or environmental cues (Waibel et al, 2006;Goldsby et al, 2010) in order to achieve specialisation.…”
Section: Introductionmentioning
confidence: 99%